Improving the post-fire performance of reinforced concrete beams with lightweight plaster - Daniel Paul Thanaraj; Varun Sabu Sam; N. Anand; Diana Andrushia; Katherine A. Cashell (Case Studies in Construction Materials, 2025)
Structural fires pose significant risks to the built environment, making fire resistance a critical design consideration for reinforced concrete (RC) structures. Elevated temperatures during fires reduce the strength and stiffness of both concrete and steel reinforcement, compromising load-bearing capacity. This experimental study evaluates the effectiveness of lightweight plaster coatings in enhancing the post-fire performance of RC members exposed to ISO 834 standard fire conditions. Two materials, expanded vermiculite (EV) and expanded perlite (EP), were examined. First, the compressive strength of concrete mixes incorporating EV or EP as partial replacements (2.5 %, 5 %, 7.5 %, and 10 %) for fine aggregates was assessed after heating durations of 30–120 min. Subsequently, structural performance was tested in RC beams across three configurations: (1) EV or EP integrated into the mix, (2) EV or EP applied as external plaster, and (3) a combination of both. A total of 54 RC beam specimens were cast, with 12 beams used for internal temperature monitoring and 42 subjected to four-point bending tests following 60, 90, and 120 min of heating. Concrete grades M20 and M50 were developed using EV or EP as partial sand replacements, while plaster layers were prepared with EV or EP mortar. Key performance indicators, including load-deflection response, ultimate load, internal temperature distribution, residual rebar yield strength, and first-crack load, were analysed. The protected M20-EP+EPC beam recorded a 62.2 % reduction in rebar temperature compared to the unprotected M20-R beam. Further, the loss of yield strength was reduced by 87.5 %, and the moment of resistance degradation was reduced by 61.1 % compared to the unprotected M20-R beam. Beams protected with EV or EP in both the mix and external plaster demonstrated superior performance, extending survival time from 45 to 120 min and improving fire resistance ratings from 15 to 60 min based on insulation criteria.